Analysis of Microbial Dynamics and Physiochemical Characteristics of Novel Sorghum Fermented Beverages - Lopez G., Victoria A. (Zamorano: Escuela Agrícola Panamericana, 2024)
Kombucha is a fermented drink of Asian origin that has been attributed with multiple health benefits and functional properties. Traditionally, this beverage is made from sweetened black or green tea and a starter culture (SCOBY). This study aims to explore the microbial dynamics and physiochemical changes during kombucha fermentation using three types of whole grain sorghum: White, Waxy, and Sumac. During fermentation, pH, °Brix, and polyphenol content were evaluated as well as the growth dynamics of lactic acid bacteria, acetic acid bacteria, and yeast. It was found that the tannin content of the sorghum varieties affected microbial growth, specifically acetic acid bacteria. In addition, there were significant differences in the polyphenol content between treatments, with Sumac sorghum kombucha exhibiting the highest polyphenol content on day seven. These findings suggest that the presence of tannins in sorghum may impact bacterial growth during Kombucha fermentation. Therefore, it is recommended to use sorghum high in tannins, such as Sumac Sorghum, for kombucha fermentation. However, further research is needed to identify the specific microbial interactions and determine the precise mechanism underlying the influence of sorghum tannins on bacterial growth.